Tracing North Atlantic Oscillation forecast errors to stratospheric origins - Kolstad, Erik W.; Wulff, Christoph O.; Domeisen, Daniela; id_orcid:0 000-0002-1463-929X; Woollings, Tim (Journal of Climate, 2020)
ISSN:0894-8755 ISSN:1520-0442